Comparative Study of Antibacterial and Phytochemical Properties of Nigerian Medicinal Plants on Salmonella bongori and Salmonella enteritidis Isolated from Poultry Feaces in Owo Local Government. Ondo State, Nigeria - , Osuntokun Oludare Temitope (Archives of Current Research International, 2015)
Salmonellosis is cause be salmonella species of bacteria namely Salmonella enteritica and Salmonella bongori. Salmonellosis is a form of food poisoning usually obtained from eating tainted meat, poultry eggs or dairy products. Conventional medicine states there is no real cure for salmonella infection, but alternative medicine may have remedies and treatments available that can reduce or eliminate the majority of symptoms if caught and treated in time. The basic objective of this research work is to determine the antibacterial and phytochemical properties of some Nigerian medicinal plants on Salmonella speciesIsolated from poultry feaces in Owo local Government as a scientific rationale behind the medicinal uses of the plants. The plant were collected from Owo reserved forest along Ute road, Ondo state and authenticated by a botanist in the Department of Biological Sciences, Achievers University, Owo. The test organism were collected from a known poultry in Owo and isolated at the Department of Microbiology, Federal Medical Centre, Owo, Ondo State. Plant extract were prepared for extraction, with four extracting medium and simple distillation method, this precede biochemical test to ascertain its authenticity. Antibacterial and Phytochemical assay using the Agar diffusion method were used. Morindalucida and Piper guineense were the most active and Nicotianatabacum and Cariaca papaya were moderately Sensitive to the test organism. Phytochemical screening shows that the plant contains some compounds like Tannin, Phenol, Alkaloid, Flavonoids, Oxalate, Saponin, and Phytate. Minerals present in plant extract (/100 g) arena (Sodium), K (Potassium), C (calcium), Mg (Magnisium), Zn (Zinc), Fe(Iron), Pb (lead), Cu (Copper), Mn (Manganese) and P (Phosporus). The research shows that Morindalucida, Piper guineense, Nicotianatabacum and Cariaca papaya are potent remedy for salmonellosis, therefore the use of medicinal plant should be encourage and the production of new antibiotic.